Probabilidade para o ensino médio - Dourado Júnior, José Nobre (2014)
This work has as objective introduce the basic concepts of the Theory of Probabilities and present notions on some probabilistic models for the student of the High School. We will begin the work presented in chapter I the notions of experiment deterministic, random experiment, sample space and events, followed by some definitions of Probability concepts that constitute the basis for this theory. In chapter II we will discuss the concepts of Conditional Probability and Independence of Events showcasing some important theorems that derive from these concepts, as well as some of its applications. In chapter III we will present in a simple way some probabilistic models discrete quite useful for shape effectively a good number of random experiments thus contributing to the calculation of the probabilities of its results. Finally, in chapter IV will be presented the probability model known as Poisson distribution, which allows us to calculate the probability that an event will occur in a given time interval or in a given spatial region.